Subtotal scapulectomy in a patient with chondroma scapula: A case report - Debbarma, Ijack; Agarwal, Saumya; Ahmed, Parvez; Garg, Apoorv Mohan; Ameer, Faisal (Indian Journal of Case Reports, 2019)
A benign chondroma (juxtacortical) is an unusual benign cartilaginous tumor. Juxtacortical chondromas, also known as periosteal chondromas, arise from the periosteum of the bones. They are thought to account for ~2% of benign bone tumors. Management of the tumor by excision in the form of total scapulectomy results in severe impairment of the upper limb function, but if all or part of the glenohumeral joint is preserved, a good function can be maintained. There is paucity in the literature about such cases. Here, we report the case of a 24-year-old male patient with chondroma of the right scapula. The patient was treated with subtotal scapulectomy and showed excellent functional outcome in terms of the range of motion of the shoulder joint.